Peranan Organisasi Pondok Pesantren (OPP) dalam Menanamkan Nilai-Nilai Pendidikan Islam di Pondok Pesantren Irsyadul Islamiyah Tanjung Medan - Harahap, Rosma Wahyuni; Sagala, Ahmad Habin; Srimulat, Fitri Endang (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2024)
This study examines the role of the Islamic Boarding School Organization (OPP) in instilling Islamic education values ​​at the Irsyadul Islamiyah Tanjung Medan Islamic Boarding School. Using a qualitative descriptive approach, this study collected data through observation, interviews, and documentation. Triangulation was used as a validity technique in this study. Data analysis techniques in this study include data reduction, data display, and drawing conclusions. The results of the study indicate that OPP plays an effective role in instilling Islamic education values ​​through various activities such as studying yellow books, preaching, al-barzanji, and yasin. The values ​​instilled include faith and piety, discipline, responsibility, Islamic brotherhood, leadership, and Islamic scientific and ethical values. Supporting factors in implementing the role of OPP include full support from the Islamic boarding school, active participation of students, and diversity of work programs. Meanwhile, inhibiting factors include limited human resources who are competent in leadership, minimal facilities and infrastructure, and low discipline of some students. This study concludes that OPP is an important instrument in the formation of the character of students in accordance with Islamic values.